Application of Animal Models in Interpreting Dry Eye Disease - Zhu, Jun; Inomata, Takenori; Shih, Kendrick Co; Okumura, Yuichi; Fujio, Kenta; Huang, Tianxiang; Nagino, Ken; Akasaki, Yasutsugu; Fujimoto, Keiichi; Yanagawa, Ai; Miura, Maria; Midorikawa-Inomata, Akie; et al. (Frontiers in Medicine, 2022)
Different pathophysiologic mechanisms are involved in the initiation, development, and outcome of dry eye disease (DED). Animal models have proven valuable and efficient in establishing ocular surface microenvironments that mimic humans, thus enabling better understanding of the pathogenesis. Several dry eye animal models, including lacrimal insufficiency, evaporation, neuronal dysfunction, and environmental stress models, are related to different etiological factors. Other models may be categorized as having a multifactorial DED. In addition, there are variations in the methodological classification, including surgical lacrimal gland removal, drug-induced models, irradiation impairment, autoimmune antibody-induced models, and transgenic animals. The aforementioned models may manifest varying degrees of severity or specific pathophysiological mechanisms that contribute to the complexity of DED. This review aimed to summarize various dry eye animal models and evaluate their respective characteristics to improve our understanding of the underlying mechanism and identify therapeutic prospects for clinical purposes.